On the Value of Estimating Human Arm Stiffness during Virtual Teleoperation with Robotic Manipulators - Buzzi, Jacopo; Ferrigno, Giancarlo; Jansma, Joost M.; De Momi, Elena (Frontiers in Neuroscience, 2017)
The use of tele-operated robotic systems is widely spreading in multiple different fields, from hazardous environments exploration to surgery. In tele-operation, users directly interact with a master device that is manipulated to achieve the task execution at the slave robot side; this interaction is fundamental both in terms of system stability and task execution performance. In this work, we propose a non-disruptive method to study the arm endpoint stiffness to evaluate how users exploited the arm kinetic redundancy to achieve stability and precision during the execution of different tasks with different master devices. Four users were asked to perform two planar trajectory following virtual tasks using a serial and a parallel link master device. The users' arm kinematic and muscular activation were acquired and combined with a user-specific musculoskeletal model to estimate the joints stiffness; through the arm Jacobian, the arm end-point stiffness was derived. The maximal stiffness values, as well as the task performance in terms of positional error, were computed. The estimated stiffness was evaluated as a function of the trajectories curvatures and the hand speed and acceleration. The results show that users modulated the arm endpoint stiffness with respect to the different tasks and interfaces, and that this modulation is influenced by the trajectory characteristics and the user's hand acceleration.